Roles of environmental variables and land usage as drivers of dung beetle assemblage structure in mopane woodland. (19th August 2013) - Davis, Adrian L. V.; Swemmer, Anthony M.; Scholtz, Clarke H.; Deschodt, Christian M.; Tshikae, B. Power
Abstract Colophospermum mopane woodland covers large areas of dry lowland savanna in southeastern Africa. Dominant land usage is conservation (45%) with the remainder mostly modified by farming. Dung beetle responses to environment (dung type, habitat, weather) and land usage (conservation, farming, mining) were examined at Phalaborwa (23.9431°S 31.1411°E) in the Phalaborwa‐Timbavati Mopaneveld, South Africa. Partitioning of gamma species richness and diversity showed lower alpha values in mine areas than in farm and conserved areas. However, between‐land usage differences in species richness, alpha diversity, abundance and biomass, showed lower significance than those between dung type and different weather. At two sampling scales, three multivariate techniques variously separated assemblages according to land usage, dung type and weather. Analysis of 21 mean samples separated clusters according to dung type (Canonical Correspondence Analysis, CCA) or mine assemblages, conserved plus farm assemblages on pig plus elephant, or cattle dung (NMDS, Factor Analysis) with shared variance of >80% and unique variance of 16–18% per cluster. In analysis of 188 samples (CCA), each overlapping dung type cluster was offset in ordinal space with congruent patterns of separation according to land usage and weather (drier days distant from moister days; conserved plus farm areas distant from early succession mine areas, which were distant from disturbed and later succession mine areas). Mining, dung types, and moist conditions were the strongest contributors to between‐assemblage differences. Compared with conserved areas, dung beetle diversity is appreciably altered by mining but only slightly altered by intensive game farming or livestock ranching with subsistence agriculture.